Solvency and profitability: the duality of the large Spanish banks between the two economic-financial crises of the 21st century - Saiz-Sepúlveda, Álvaro; Orden-Cruz, Carmen; Hernández-Tamurejo, Álvaro (Frontiers in Applied Mathematics and Statistics, 2024)
A retrospective view of the "subprime mortgage" crisis enables us to assess the actions of banks, both those prompting the genesis of the crisis and those resulting from subsequent actions aimed at resolving it and rebooting the economy. However, given the fact that the crisis is framed by the sudden appearance of another outside the established parameters of the post-recession boom, we are able to analyze whether the actions adopted by regulators were as effective as initially thought. From the numerous parameters described in the literature reviewed (and in some cases cited in the bibliography), a series of ratios have been determined that allow us to glimpse the connections between the solvency and profitability of financial institutions. From a detailed analysis of the data, valid conclusions can be obtained, at least in terms of the sample under analysis (three institutions representing more than 60% of the national banking sector), and which, due to their importance and representativeness, can also be extrapolated to the national and European financial system as a whole. Limitations: This study presents limitations derived from the sample observed. A greater number of banks would have made it possible to verify the study’s assertions.